Effectiveness of a contact-based anti-stigma intervention for police officers. (May 2021) - Wittmann, Linus; Dorner, Robert; Heuer, Imke; Bock, Thomas; Mahlke, Candelaria
Abstract: Introduction: Police force interaction rates with individuals with mental health conditions are on the rise. International research reveals that the presence of a mental health condition increases the risk for detention and use of force by police officers. Stigmatization of individuals with mental health conditions as dangerous and unpredictable is assumed to have an impact on the likelihood of police use of force. The following study examines a trialogical intervention to reduce stigmatization of individuals with a diagnosis of schizophrenia in a police officer sample. Method: 1318 police officers participated in a trialogical contact-based intervention with the aim to reduce stigmatizing attitudes and beliefs. Emotional reactions, stereotypes and social distance were assessed prior to and after the intervention in a one-group design. Results: Negative stereotypes were positively associated with social distance in individuals with a diagnosis of schizophrenia and were positively associated with anxiety. Dependent sample t -test revealed reduced anxiety towards individuals with a diagnosis of schizophrenia, less negative stereotypes, and less social distance post intervention. All results were significant, and all effect sizes showed a small to moderate effect. Conclusions: Trialogical contact-based, short-term anti-stigma interventions appear to reduce stigmatizing attitudes towards individuals with mental health conditions in a large police force sample. A missing control group is a key study limitation. Further research is needed to examine the effectiveness of the intervention in a randomized-controlled trial. However, the results clearly suggest that anti-stigma interventions could be beneficially introduced into police training. Highlights: Police officers' stereotypes towards individuals with a diagnosis of schizophrenia are linked to increased social distance and anxiety Trialogical interventions can reduce stigmatization of individuals with a serious mental illness and should be implemented in police training Focusing on an anti-stigma philosophy, the intervention proposed in this article is a promising addition to de-escalation trainings